Discrepancy and Proportionality in the Maturidi and Samarkandi Doctrinal Views (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
In the second half of the 9th century, a new school appeared in the history of the Samarkand kalom School: Abu Sulaiman This is associated with the name of student of Abu Sulaiman Juzjani's disciple Abu Bakr Juzjani and his hanafi students. Since the works of these two schools in the field of the kalom have not reached us, it is difficult to express any opinion about their contribution to the development of this discipline. But the creations of representatives of this school – Abu Mansur Moturidi and Hakim Samarkandi - indirectly indicate that the range of knowledge of their teachers is much wider and more significant.